2021
DOI: 10.21037/hbsn-21-327
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive liver resection for huge (≥10 cm) tumors: an international multicenter matched cohort study with regression discontinuity analyses

Abstract: Background: The application and feasibility of minimally invasive liver resection (MILR) for huge liver tumours (≥10 cm) has not been well documented.Methods: Retrospective analysis of data on 6,617 patients who had MILR for liver tumours were gathered from 21 international centers between 2009-2019. Huge tumors and large tumors were defined as tumors with a size ≥10.0 cm and 3.0-9.9 cm based on histology, respectively. 1:1 coarsened exact-matching (CEM) and 1:2 Mahalanobis distance-matching (MDM) was performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 39 publications
2
17
0
Order By: Relevance
“…Comparison with the group of patients with smaller metastases shows that laparoscopic resection of large liver tumors in expert hands can achieve similar surgical outcomes. The higher blood loss seen in this series is in line with the previous studies on laparoscopic liver resection for large liver tumors [ 32 , 34 ]. The worse overall survival in the large tumor group was somehow expected since the size of the tumor is a prognostic factor and has been included in clinical scoring systems [ 35 , 36 ].…”
Section: Discussionsupporting
confidence: 91%
“…Comparison with the group of patients with smaller metastases shows that laparoscopic resection of large liver tumors in expert hands can achieve similar surgical outcomes. The higher blood loss seen in this series is in line with the previous studies on laparoscopic liver resection for large liver tumors [ 32 , 34 ]. The worse overall survival in the large tumor group was somehow expected since the size of the tumor is a prognostic factor and has been included in clinical scoring systems [ 35 , 36 ].…”
Section: Discussionsupporting
confidence: 91%
“…In the study, comparison between MILR for 174 huge tumors with 174 large (3–9.9 cm) tumors demonstrated not unexpectedly poorer outcomes in terms of blood loss, major morbidity and length of stay. However, the perioperative outcomes of MILR for huge tumors compared favourably with previous studies reporting on open LR for huge tumours ( 20 ).…”
Section: Discussionsupporting
confidence: 51%
“…We had previously published an international multicenter study on the application of MILR for huge liver tumours showed that with careful patient selection, MILR could be performed safely in this subset of patients. Many participating specialized centers with expertise had demonstrated the feasibility and safety of resecting huge liver tumours by the minimally invasive approach ( 20 ). In the study, comparison between MILR for 174 huge tumors with 174 large (3–9.9 cm) tumors demonstrated not unexpectedly poorer outcomes in terms of blood loss, major morbidity and length of stay.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To select patients with a low-preoperative risk profile for benchmarking,2 only patients aged between 18 and 70 years old5 and with a low American Society of Anesthesiology classification ≤2 were included 5. Patients with very large tumors ≥10 cm,20 Child’s B liver cirrhosis or portal hypertension were excluded 17,21. We also excluded patients who had L-LR for gallbladder cancer, donor hepatectomies, previous liver resections (repeat liver resections),22 associating liver partition and portal vein ligation for staged hepatectomy,11 bilioenteric anastomoses, hilar lymph node clearance, and those who underwent L-LR with concomitant major operations such as colectomies, bowel resections, and stoma reversals 11,23,24.…”
Section: Methodsmentioning
confidence: 99%